2011
DOI: 10.1074/jbc.c111.245324
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Membrane-tethering GRASP Domain Reveals a Unique PDZ Ligand Interaction That Mediates Golgi Biogenesis

Abstract: Biogenesis of the ribbon-like membrane network of the mammalian Golgi requires membrane tethering by the conserved GRASP domain in GRASP65 and GRASP55, yet the tethering mechanism is not fully understood. Here, we report the crystal structure of the GRASP55 GRASP domain, which revealed an unusual arrangement of two tandem PDZ folds that more closely resemble prokaryotic PDZ domains. Biochemical and functional data indicated that the interaction between the ligand-binding pocket of PDZ1 and an internal ligand o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
145
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(151 citation statements)
references
References 23 publications
5
145
1
Order By: Relevance
“…This construct of GRASP55 is very similar to GRASP65(1-210) and seven residues longer than the one used in previous studies, in which the structure of the tandem PDZ domains of GRASP55 was reported (17). The conformation of the PDZ domains in our structure of GRASP55 is nearly identical to that in the previous structure (Fig.…”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…This construct of GRASP55 is very similar to GRASP65(1-210) and seven residues longer than the one used in previous studies, in which the structure of the tandem PDZ domains of GRASP55 was reported (17). The conformation of the PDZ domains in our structure of GRASP55 is nearly identical to that in the previous structure (Fig.…”
Section: Resultssupporting
confidence: 75%
“…Our crystal structures show that the CT of the GRASP proteins interacts with the PDZ1 domain in just such a manner; even the unconventional PDZ2-PDZ2 association generates an antiparallel ␤-sheet using the two ␤5s and utilizes hydrophobic packing via a Phe from ␣2. In the previous structural studies of GRASP55, the PDZ1 domain was speculated to bind to an internal ligand, residues 196 -199 of ␤5 in the PDZ2 domain, whereas the PDZ2 domain engaged the C terminus of GM130 (17). Consistent with this proposal, hydrophobic residues from ␣2 and ␤5 of the PDZ1 domain (Leu-59 and Ile-100 in GRASP55) and part of ␤5 of the PDZ2 domain (residues 196 -199) were shown to be critical for the tethering ability of GRASP55 (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations